2022
DOI: 10.1186/s41239-021-00313-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning analytics dashboard: a tool for providing actionable insights to learners

Abstract: This study investigates current approaches to learning analytics (LA) dashboarding while highlighting challenges faced by education providers in their operationalization. We analyze recent dashboards for their ability to provide actionable insights which promote informed responses by learners in making adjustments to their learning habits. Our study finds that most LA dashboards merely employ surface-level descriptive analytics, while only few go beyond and use predictive analytics. In response to the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 47 publications
0
19
0
3
Order By: Relevance
“…However, it is essential to consider the evolving nature and potential of LADs. Research by Susnjak et al (2022) propose advancing LADs from descriptive to predictive and prescriptive analytics to enhance self‐reflection and guide learners more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to consider the evolving nature and potential of LADs. Research by Susnjak et al (2022) propose advancing LADs from descriptive to predictive and prescriptive analytics to enhance self‐reflection and guide learners more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the authors demonstrated that their LAD helped improve learning effectiveness. Susnjak et al (2022) analyzed recent LADs for their ability to provide actionable insights using a literature review and proposed an LAD that addressed many of the shortcomings. Their LAD proposed integrated descriptive, predictive, and data-driven prescriptive analytics into one display.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies either focused on improving teaching and learning (e.g., Schwendimann et al, 2016), or verifying an LAD's effectiveness in comprehension through the educational practice (Wang & Han, 2021). Susnjak et al (2022) reviewed 17 dashboards targeting learners and instructors. The authors observed that all LADs incorporated interface-level descriptive analytics, usually in the form of graphical displays depicting students' own information and comparisons with others.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that the use of predictive models can be a useful approach for determining which students to prioritize (Hall et al, 2021;Susnjak et al, 2022;Yu et al, 2020). Institutions are now refining their student success approaches even more by moving from using data to predict which students need assistance to using data to also prescribe specific interventions (Chen & Upah, 2018;Thompson et al, 2018).…”
Section: Advancing From Prediction To Prescription: Strategies For Pr...mentioning
confidence: 99%